THE MORAL HARASSMENT IN HEALTH PROFESSIONALS IN AN ORGANIZATION PUBLIC - Daniel, Hélcia; Macêdo, Kátia Barbosa (IJRDO-Journal of Applied Science, 2015)
The text aims to discuss and present data on indicators ofsuffering and bullying in a public institution with group of professionals inhealthcare. We used the theoretical and methodological approach ofpsychodynamic clinical work, which dealt with bullying in the emphasis thecentrality of work seen in a psychic constitution important factor of the individualand subjective mobilization of this subject from their relationships at work.Bullying is abusive behavior, manifested in behavior, words and actions thatmay have negative effects on the psychological and physical. Thus, it analyzesthe experiences of suffering caused by bullying a group of professionals,discussing its causes and consequences in the workplace. Guiding questionswere prepared on the categories of psychodynamic and clinical workdemonstrating the subjective mobilization and bullying as the central element ofthe study. As Results revealed the incidence of bullying at different levels ofhierarchy and peer and its negative consequences, both in mental health, suchas anxiety, anger, low esteem, as physical conditions such as illness, theremoval of work, was noted aggravating psychological conditions in someparticipants, it was realized too, was the organization of work, required goalsand results involving overload, pressure on results among others, greatlyexacerbate the presence on condition of bullying in the group . Although as aresult the lack of recognition was evident, and the condition of lack of speechand improvement actions by the agents causing discouragement andNegligence thereof.